C-4-metoksifenilkaliks[4]pirogalaril Dodekasinamat: Sintesis dan Uji Pendahuluan sebagai Bahan Aktif Tabir Surya - Harizal Harizal; Jumina Jumina; Tutik Dwi Wahyuningsih (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
Synthesis and preliminary study of C-4-methoxyphenyl[4]pyrogallaryl dodecacinnamate were successfully performed. Synthesis of target molecule was conducted in two steps including preparation of calix[4]pyrogallarene derivative, and O-cinnamoylation of the calix[4]pyrogallarene. The product obtained was pre-evaluated as sunscreen active compound through UV spectroscopy (UV absorbance profile, maximum wavelength, and molar absorption coefficient), and photostability tests. The results of evaluation indicated dominant absorbance in UVC/UVB region with exceptionally high molar absorption coefficient. In other side, target molecule has relatively low photostability in which the UV absorbance decreased 47% after 30 minutes irradiation. The main factor for this lowering was due to the close distance between each cinnamate groups.